Association of residual pulmonary hypertension with survival after pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension. (27th May 2022) - Kallonen, Janica; Korsholm, Kasper; Bredin, Fredrik; Corbascio, Matthias; Jønsson Andersen, Mads; Ilkjær, Lars Bo; Mellemkjær, Søren; Sartipy, Ulrik
Abstract: This study investigated whether residual pulmonary hypertension (PH), defined as early postoperative mean pulmonary artery pressure (mPAP) of ≥30 mmHg, after undergoing pulmonary endarterectomy (PEA) for chronic thromboembolic pulmonary hypertension (CTEPH) was associated with long‐term survival. All patients who underwent PEA for CTEPH at two Scandinavian centers were included in this study. Baseline characteristics and vital statuses were obtained from patient charts and national health‐data registers. The patients were then categorized based on residual PH measured via right heart catheterization within 48 h after undergoing PEA. Crude and weighted flexible parametric survival models were used to estimate the association between residual PH and all‐cause mortality and to quantify absolute survival differences. From 1992 to 2020, 444 patients underwent surgery. We excluded 6 patients who died on the day of surgery and 12 patients whose early postoperative pulmonary hemodynamic data was unavailable. Of the total study population ( n  = 426), 174 (41%) and 252 (59%) patients had an early postoperative mPAP <30 and ≥30 mmHg, respectively. After weighting, there was a significant association between residual PH and all‐cause mortality (hazard ratio: 2.49; 95% confidence interval [CI]: 1.60–3.87), and the absolute survival difference between the groups at 10 and 20 years was –22% (95% CI: –32% to –12%) and–32% (95% CI: –47% to –18%), respectively. A strong and clinically relevant association of residual PH with long‐term survival after PEA for CTEPH was found. After accounting for differences in baseline characteristics, the absolute survival difference at long‐term follow‐up was clinically meaningful and imply careful surveillance to improve clinical outcomes in these patients. Early postoperative right heart catheter measurements of mPAP seem to be helpful for prognostication following PEA for CTEPH.